THE ROLE OF GENDER COMMUNICATION IN ACHIEVING GENDER PARITY: THE LEGAL CHALLENGES OF TODAY - Bobrova, J. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Initially equality seems to be a very simple and obvious category for understanding, however if this has been actually the case we would be living in a perfect society. Equality always exists together with inequality. The assurance and implementation of gender parity is an up-to-date issue not only for Ukraine but for all democratic countries. The practical implementation of the principle of gender equality is to be set forth by increasing the level of democracy of the very same gender-legal relations within a society and their further development based on the principles of parity for both genders. The issue is to be settled within a complex approach, considering the theoretic achievements in the issue of gender, but also the practices of its implementation in all the spheres of social life. In this context it is necessary to develop a strategy of gender policy in a state and systematically assess the state of its implementation. The achievement of gender symmetry in Ukraine is impossible without the appropriate fixation of provisions within the norms of current legislation, and the establishment of a legal state, the development of civil society, the perspectives of European integration provide for the necessity to establish gender legislation and the effective policy of equal rights for men and women. The author of the article analyses the normative fixation of the mechanism of gender communication and its role, the probability of achieving gender symmetry in the Concept of communication in the sphere of gender equality, that has been approved by the decree of the Cabinet of Ministers of Ukraine on 16 of September 2020 № 1128-р. The analysis is aimed at the ways of improving understanding the essence of gender issues, instruments, resources and levels of gender communication stipulated in the Concept. Their critical assessment is provided with regard to the possibilities of practical implementation in the course of the years 2020-2025. It is obvious that the gender issue in Ukraine is to be settled in a complex and consequent manner, considering the positive experience of foreign countries and the national traditions and mentality of the Ukrainian nation, in order to avoid hasty decisions and prevent taking unpopular steps.